2020
DOI: 10.3390/w12123366
|View full text |Cite
|
Sign up to set email alerts
|

Drought Monitoring Based on Remote Sensing in a Grain-Producing Region in the Cerrado–Amazon Transition, Brazil

Abstract: Drought is a natural disaster that affects a country’s economy and food security. The monitoring of droughts assists in planning assertive actions to mitigate the resulting environmental and economic impacts. This work aimed to evaluate the performance of the standardized precipitation index (SPI) using rainfall data estimated by orbital remote sensing in the monitoring of meteorological drought in the Cerrado–Amazon transition region, Brazil. Historical series from 34 rain gauge stations, in addition to indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Drought indices are important instruments for defining and monitoring drought because they simplify complex meteorological functions and can quantify climatic abnormalities in terms of severity, length, and frequency [38,39]. Moreover, over the last few decades, many studies have been conducted to monitor the drought in Ethiopia, and most of these studies are SPI-based drought [40,41] analyses based on location-specific observed or stationed rainfall data. Reconnaissance drought index (RDI) [42], normalized difference vegetation index (NDVI), land surface temperature (LST), vegetation condition index (VCI), temperature condition index (TCI), and vegetation health index (VHI) [43] methods were used to measure drought, and the Mann-Kendall and Sen's slope test to detect rainfall and temperature trend over the central Rift Valley and Gamo Zone regions of Ethiopia, which depend on weather station data and vegetation condition.…”
Section: Introductionmentioning
confidence: 99%
“…Drought indices are important instruments for defining and monitoring drought because they simplify complex meteorological functions and can quantify climatic abnormalities in terms of severity, length, and frequency [38,39]. Moreover, over the last few decades, many studies have been conducted to monitor the drought in Ethiopia, and most of these studies are SPI-based drought [40,41] analyses based on location-specific observed or stationed rainfall data. Reconnaissance drought index (RDI) [42], normalized difference vegetation index (NDVI), land surface temperature (LST), vegetation condition index (VCI), temperature condition index (TCI), and vegetation health index (VHI) [43] methods were used to measure drought, and the Mann-Kendall and Sen's slope test to detect rainfall and temperature trend over the central Rift Valley and Gamo Zone regions of Ethiopia, which depend on weather station data and vegetation condition.…”
Section: Introductionmentioning
confidence: 99%
“…One of the problems of rainfed agriculture productivity is prolonged drought, lack of rainfall, and lack of water supply in the soil during the vegetative growth phase [1], [2], [3], [4]. In addition, high temperatures during the ripening phase can reduce the conversion yield of sucrose to fructose and glucose [5].…”
Section: Introductionmentioning
confidence: 99%
“…NRT SPPs are evaluated at various regions, such as China [24][25][26], Europe [27,28], South America [29], Pakistan [30], the United Arab Emirates [31], Peruvian Andes [32], and Peninsular Malaysia [33]; various basins, such as the Yellow River Source Basin in China [34], Kinu Basin in Japan [35], Lower Colorado River Basin in Texas [36], Ottawa Basin in Canada [37], and Chindwin Basin in Myanmar [38]; analyzed insight of NRT SPP performance at various aspects, such as climatology [39], seasons [40], extreme events [29,41], and utilization purposes (e.g., flood simulation [32,42], crop forecasting [43,44], drought monitoring [45], and landslides [46]).…”
Section: Introductionmentioning
confidence: 99%